2016
DOI: 10.1016/j.sna.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of strain sensors based on PEDOT:PSS and silver nanoparticles inks deposited on polymer substrate by inkjet printing

Abstract: a b s t r a c tRecently, inkjet printing technology has received growing attention as a method to produce low-cost large-area electronics, sensors, and antennas on polymer substrates. This technology relies on printing techniques to deposit electrically functional materials onto polymer substrates to fabricate electronic components or sensing elements. In this paper, we applied an inkjet printed technology for the development and characterization of films on a polymer substrate aiming at giving design consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 30 publications
2
54
0
1
Order By: Relevance
“…These results are in accordance with the results reported by Vipin et al [22]. Like for polymer-based resistive sensors [23,24], we can suppose that the resistance is affected by the stress relaxation of the materials and by the viscoelastic effects, mainly in the first cycles.…”
Section: Stretch Sensor Testssupporting
confidence: 93%
“…These results are in accordance with the results reported by Vipin et al [22]. Like for polymer-based resistive sensors [23,24], we can suppose that the resistance is affected by the stress relaxation of the materials and by the viscoelastic effects, mainly in the first cycles.…”
Section: Stretch Sensor Testssupporting
confidence: 93%
“…While this effect makes for higher gauge factors, it is also a cause for hysteresis effects and drift in the absolute value of the strain gauges. Drift is said to be the result of permanent cracks in the conductive track on the microscale (Borghetti et al, 2016;Song et al, 2017;Boland et al, 2014).…”
Section: Infused Conductorsmentioning
confidence: 99%
“…On the contrary, inkjet printing is a mask-less method in which moving nozzles deposit ink drops on demand based on pattern design. The ability to print complex patterns with high spatial resolution and excellent printing consistency allows inkjet printing to be used as a rapid prototyping tool for printed electronics [10]. However, the inks for inkjet printing are currently limited to nanoparticle (NP)-based solutions due to the compatibility issue between nozzle and ink which often causes nozzle clogging [5].…”
Section: Introductionmentioning
confidence: 99%
“…Bruno explored a cost-effective method to make prototype strain sensors using inkjet printing [5]. Borghetti studied mechanical behaviors of PEDOT:PSS and silver NP strain sensors on a polyimide substrate [10]. However, none of these studies reported the mechanical reliability (i.e.…”
Section: Introductionmentioning
confidence: 99%